1997
DOI: 10.1103/physrevb.56.2258
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-mechanical calculation of H on Ni(001) using a model potential based on first-principles calculations

Abstract: First-principles density-functional calculations of hydrogen adsorption on the Ni ͑001͒ surface have been performed in order to get a better understanding of adsorption and diffusion of hydrogen on metal surfaces. We find good agreement with experiments for the adsorption energy, binding distance, and barrier height for diffusion at room temperature. A model potential is fitted to the first-principles data points using the simulated annealing technique and the hydrogen band structure is derived by solving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 41 publications
2
31
0
1
Order By: Relevance
“…While on Ni 4 and Ni 6 clusters the models with three-fold coordination of H converged to bridge positions of the impurity, for Ni 5 we located one minimum with a threefold coordinated H. The BE(H) of that latter structure was 11 kJ/mol lower than the most stable bridge position. The opposite trend, a higher stability of H on three-fold sites (fcc, hcp) was calculated with periodic slab models of the low-index single-crystal surfaces Ni (111) and Ni(100) [77][78][79][80]. Bridge coordination of a hydrogen ligand to a metalmetal bond is also preferred in the case of tetrahedral Pd 4 (Fig.…”
Section: Clusters With a Single Hydrogen Impuritymentioning
confidence: 99%
See 1 more Smart Citation
“…While on Ni 4 and Ni 6 clusters the models with three-fold coordination of H converged to bridge positions of the impurity, for Ni 5 we located one minimum with a threefold coordinated H. The BE(H) of that latter structure was 11 kJ/mol lower than the most stable bridge position. The opposite trend, a higher stability of H on three-fold sites (fcc, hcp) was calculated with periodic slab models of the low-index single-crystal surfaces Ni (111) and Ni(100) [77][78][79][80]. Bridge coordination of a hydrogen ligand to a metalmetal bond is also preferred in the case of tetrahedral Pd 4 (Fig.…”
Section: Clusters With a Single Hydrogen Impuritymentioning
confidence: 99%
“…The BE(H) values of these cluster compounds are 42-75 kJ/mol larger than the binding energy per metal atom of the corresponding bare Ni clusters. The BE of H at a bridge position of the modeled clusters is 20-50 kJ/mol higher than on Ni(100) and Ni (111) surfaces in the same adsorption position, where values from 255 to 264 kJ/mol had been calculated with periodic slab models (and the PW91 gradient-corrected density functional) [77][78][79]. While on Ni 4 and Ni 6 clusters the models with three-fold coordination of H converged to bridge positions of the impurity, for Ni 5 we located one minimum with a threefold coordinated H. The BE(H) of that latter structure was 11 kJ/mol lower than the most stable bridge position.…”
Section: Clusters With a Single Hydrogen Impuritymentioning
confidence: 99%
“…The bulk Ni-Ni parameters were fitted to the lattice constant a = 3.52 Å , the nearest neighbour distance r 0 = 2.49 Å , cohesive energy E coh = À4.44 eV and bulk modulus B = 1.17 eV/Å 3 . The H-Ni parameters of MBA potential were fitted to the DFT data given by Mattsson et al [12]. The fitted quantities are the adsorption energy of the hollow site, E ads = 2.8 eV, the equilibrium distance from the surface at hollow site r a = 0.5 Å and the energy barrier between the hollow sites through the bridge site, E barr = 0.14 eV.…”
Section: Many-body Alloy Potentialmentioning
confidence: 99%
“…Hydrogen interactions are considered to be simple and therefore well suited for fundamental research [1]. In particular, the light mass of hydrogen emphasizes quantum effects [2][3][4][5], which are used to explain peculiar adsorbate diffusion [6][7][8][9][10][11][12], vibrational observations [6], electron-energy loss spectra [13,14], low-energy electron diffraction [13,14], photoemission [14], helium scattering [15], thermal desorption [7], linear optical diffraction [16] and field emission [16,17]. Furthermore, it has been shown that quantum effects are essential in understanding the phenomena of H interactions on Ni surface [11,13,18], and, H on metal surfaces provides a unique opportunity to observe the crossover from quantum to classical dynamics at elevated temperatures [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 In line with this, it has been shown in recent years from both sides of experiment and theory that due to the small mass of hydrogen, it shows quantum effects, such as energy dispersion, tunneling, and delocalization on a solid surface. [2][3][4][5][6][7][8][9] The behavior of hydrogen on the Cu surface has been studied through several different approaches-in experimental studies for example, by high resolution electron energy loss spectroscopy ͑HREELS͒, [10][11][12] low energy electron diffraction, 10,13 and scanning tunneling microscope ͑STM͒ based inelastic electron tunneling spectroscopy ͑IETS͒ 14 and in theoretical studies, by density functional theory ͑DFT͒ based first principles calculations for electronic states [3][4][5][6][7][8][9][15][16][17][18] and quantum dynamics simulations for dissociative adsorption of hydrogen molecules, hydrogen diffusion, absorption and associative desorption. 3,4,[19][20][21][22][23] The behavior of a hydrogen atom on Cu͑100͒ has been investigated theoretically by Lai et al, 8 Sundell et al, 9 and Kua et al, 15 and on Cu͑110͒ by Bae et al 16 Save for the latter, these studies have treated hydrogen atom motion from a quantum mechanical perspective.…”
Section: Introductionmentioning
confidence: 99%